EXISTING METHODS OF PERFORMANCE RECOVERY WELLS - , А. М. (Municipal economy of cities. Series: «Economy science», 2013)
We give the existing methods of recovery performance of wells evaluated their performance by studying the kinetics dekolmatatsiyi filters pryfiltrovyh zone wells and selection of the most effective chemical reagent depending on the composition kolmatanta.